Las ventas y los resultados del ejercicio de la empresa Socopur S.A.C. periodo 2019 - 2021 - Rodríguez Mori. Werner Antonio (2023)
Modern administration postulates that higher sales do not necessarily imply growth in profits, but rather proper cost management. The objective of this doctoral thesis is to establish the existence of a relationship between sales and the results of the year of the company SOCOPUR SAC., corresponding to the year series between 2019 and 2021; that is, one year before the pandemic, another during the pandemic, and the last one after the pandemic. The type of research is Quantitative - Correlational and has a Non-Experimental design. It is concluded that there is a direct relationship between the sales and the operating results of the company during the years, since the Correlation Coefficient was r = 0.986347411; and the Determination Coefficient was R2 = 0.972881216. Sales had a variable behavior throughout the 36 months covered by the study, with July 2020 being the month in which the highest value was recorded, amounting to S/. 4,584,933.00; thanks to the gradual reopening of the economy after the closure of March of the same year. The most sold products were Tires and Tubes, having invoiced the amount of S/. 24,815,935.44 (23.15%); followed by Gears and Transmission Chains with S/. 16,598,119.83 (15.49%); and in third place Spare of Motorcycle with S/. 13,742,85.49 (12.82%); adding the three groups 51.46% of sales. The results of the operation were also variable.